Art from Köln. - Tate Gallery, Liverpool (Liverpool : Tate Gallery, 1989)
Sander, August ; Chargesheimer ; Richter, Gerhard ; Polke, Sigmar ; Rosenbach, Ulrike ; Näher, Christa ; Gruber, Bettina ; Vedder, Maria ; Kiecol, Hubert ; Trockel, Rosemarie ; vom Bruch, Klaus ; Odenbach, Marcel ; Dahn, Walter ; Locher, Thomas
Art from Köln, Tate Gallery Liverpool, 11 September - 23 October 1988
boek